Detachment, displacement and re-attachment activity in a freshwater byssate mussel (Limnoperna fortunei): the effects of light, temperature and substrate orientation - Duchini, Daniela (2015)
The ability of the freshwater bivalve Limnoperna fortunei to voluntarily detach from the substratum, crawl and reattachas a function of illumination, temperature, substratum orientation, and mussel size was investigated. Thirty-two per centof the 879 experimental animals detached and reattached elsewhere at least once during five- to eight-day experiments.The proportions of mobile mussels were significantly higher in permanent darkness than under permanent illumination.Displacement distances were also higher in darkness, but statistical differences with illuminated individuals wereinconclusive. No evidence of circadian rhythms was detected. Mobile mussels were often significantly smaller thannon-mobile individuals. It was not possible to detect the effect of water temperature (22°C and 31°C), or substratumorientation (topside and underside) on mussel mobility, but because the power of the statistical tests was low, futureexperiments are needed to confirm this result. The ability of mussels to voluntarily detach and reattach elsewhere hasimportant implications for biofouling control.